Determinan Matrik 3x3 dengan Metode Doolittle - Gita Lestari (Jurnal Pustaka Cendekia Pendidikan, 2024)
The matrix is one of the basic materials for studying mathematics, especially algebraic problems. This matrix problem is familiar to students because the matrix has been studied since they were in high school. Matrix calculation is an important topic and is often used in mathematical applications. Matrix is used in solving various problems. The matrix has a shape and size or matrix order. Among them are square matrices of size n x n, identity matrices, upper and lower triangular matrices, symmetrical matrices, diagonal matrices, singular and non-singular matrices. While the size of the matrix (matrix order) is determined by the number of rows and columns of a matrix.